Risk factors and prognostic criteria in 230 patients with influenza A (H1N1) infection - Nancy M. Abdelaty (Egyptian Journal of Chest Disease and Tuberculosis, 2013)
Background: Data on risk factors for severe outcomes from 2009 pandemic influenza A (H1N1) virus infection are limited outside of developed countries. Aim of the study: To evaluate the characteristics and outcomes of patients with 2009 pandemic influenza A (H1N1) in hospitalized patients in RCH, KSA and to identify factors associated with severe outcome. Patients and methods: We reviewed medical charts to collect data from patients hospitalized and tested for the presence of 2009 pandemic (H1N1) infection based on clinical suspicion during the period from July 2009 through December 2009, and we analyzed factors associated with severe illness (defined as illness requiring intensive care unit admission or resulting in death). Results: According to our case definition, there were 176 cases of positive pandemic influenza A (H1N1) and 54 negative cases for pandemic influenza A (H1N1). Common presenting symptoms were fever (95% of patients), sore throat (90%), and cough (83%). Laboratory findings included significant elevated levels of lactate dehydrogenase and creatine phosphokinase in pandemic influenza A (H1N1) positive cases in addition to leucopenia, lymphopenia, and neutropenia. Incidence of diarrhea was (25%), and vomiting was (21.5%).The mortality rate was 1.13%. Factors contributing to severe outcome were young age, female sex, dyspnoea, leucopenia, neutropenia, lymphopenia, high creatine phosphokinase level, and high lactate dehydrogenase level. On multivariate analysis, creatine phosphokinase level and lactate dehydrogenase were risk factors for severe outcome. Conclusions: Risk factors for severe 2009 H1N1 illness were similar to those observed in developed countries. A significant number of relatively young and previously healthy positive patients might develop severe disease associated with a robust inflammatory reaction.